Performance of gilts and castrates when fed separately on two different levels of feeding - Kuan, K. K.; Mak, T. K. (Universiti Pertanian Malaysia, 1982)
Twenty castrated male pigs and twenty gilts initially averaging 52 kg were fed individually so that that performance and carcass quality of pigs fed on a scale based on ad libitum feeding could be compared to those fed on a restricted regime under local environmental conditions. Pigs fed on a scale based on ad libitum feeding showed a significantly faster growth rate and had more back fat compared to pigs on restricted feeding. For each 1% of feed restriction there was a corresponding 1%reduction in average daily gain and 0.91%reduction in average back fat thickness. Gilts excelled over castrates in performance and carcass quality .. the former grew faster, were more efficient in feed utilization and produced carcasses with less back fat and larger loin eye area compared to the latter. The digestible energy intake of pigs was less than animals of similar live weight in temperate environments. In order to improve efficiency of production, it is suggested that castrates and gilts be fed separately during the finishing stage with the castrates subjected to a more severe level of feed restriction in order to limit fat deposition